Determine The Optimum Conditions for Producing Prodigiosin Pigment from Serratia Marcescens Clinical and Environmental Isolates - Aseel Razak Al-Rekaabi (Jurnal MIPA dan Pembelajarannya, 2026)
Serratia marcescens isolates were isolated from various clinical and environmental sources, the 60 sample include 12 isolates were obtained from diverse clinical specimens and environment and all isolates produced prodigiosin. Following multiple screening stages, the local isolate Serratia marcescens SM5 was chosen due to its high prodigiosin dye production. Environmental and clinical samples were cultured on MacConkey agar medium. The media was incubated at 37 °C for 24 hours. The color and shape of the colonies in the culture media, as well as the cell shape and pigmentation in the microscopic examination, were used to determine the phenotypic traits. To confirm the type of isolates, biochemical tests were done. and the Api 20 E. method was used to identify the isolates. The best conditions for producing prodigiosin dye were discovered. The maximum dye output was discovered while employing a peptone-glycerol medium at pH 8 and 30 °C for 72 hours.